Proteomic and Biological Analysis of an In Vitro Human Endothelial System in Response to Drug Anaphylaxis - Yuste-Montalvo, Alma; Fernandez-Bravo, Sergio; Oliva, Tamara; Pastor-Vargas, Carlos; Betancor, Diana; Goikoetxea, María José; Laguna, José Julio; López, Juan Antonio; Alvarez-Llamas, Gloria; Cuesta-Herranz, Javier; Martin-Lorenzo, Marta; Esteban, Vanesa (Frontiers in Immunology, 2021)
Anaphylaxis is a life-threatening systemic hypersensitivity reaction. During anaphylaxis, mediator release by effector cells causes endothelial barrier breakdown, increasing vascular permeability and leakage of fluids, which may lead to tissue edema. Although endothelial cells (ECs) are key players in this context, scant attention has been paid to the molecular analysis of the vascular system, and further analyses of this type are necessary, especially in humans. The protein expression pattern of human microvascular ECs was analyzed in response to sera from anaphylactic patients (EC-anaphylaxis) and sera from non-allergic subjects (EC-control) after 2 hours of contact. Firstly, a differential quantitative proteomic analysis of the protein extracts was performed by mass spectrometry using an isobaric labeling method. Second, the coordinated behavior of the identified proteins was analyzed using systems biology analysis (SBA). The proteome of the EC-anaphylaxis system showed 7,707 proteins, of which 1,069 were found to be significantly altered between the EC-control and EC-anaphylaxis groups (p-value < 0.05). Among them, a subproteome of 47 proteins presented a high rate of change (|ΔZq| ≥ 3). This panel offers an endothelial snapshot of the anaphylactic reaction. Those proteins with the highest individual changes in abundance were hemoglobin subunits and structural support proteins. The interacting network analysis of this altered subproteome revealed that the coagulation and complement systems are the main biological processes altered in the EC-anaphylactic system. The comprehensive SBA resulted in 5,512 functional subcategories (biological processes), 57 of which were significantly altered between EC-control and EC-anaphylaxis. The complement system, once again, was observed as the main process altered in the EC system created with serum from anaphylactic patients Findings of the current study further our understanding of the underlying pathophysiological mechanisms operating in anaphylactic reactions. New target proteins and relevant signaling pathways operating in the in vitro endothelial-serum system have been identified. Interestingly, our results offer a protein overview of the micro-EC-anaphylaxis environment. The relevance of the coagulation, fibrinolytic, contact, and complement systems in human anaphylaxis is described. Additionally, the untargeted high-throughput analysis used here is a novel approach that reveals new pathways in the study of the endothelial niche in anaphylaxis.